2005
DOI: 10.1593/neo.04430
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α and the Glycolytic Phenotype in Tumors

Abstract: Metastatic tumors generally exhibit aerobic glycolysis (the Warburg effect). The advent of [18F]fluorodeoxyglucose positron emission tomography imaging, coupled with recent findings linking hypoxia-inducible factor (HIF-1alpha) overexpression to aggressive cancers, has rekindled an interest in this aspect of tumor metabolism. These studies explore the role of HIF-1alpha in human breast cancer lines and its relationship to glycolytic regulation. Here we demonstrate that, under normal oxygen conditions, nonmetas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
164
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(173 citation statements)
references
References 37 publications
7
164
0
2
Order By: Relevance
“…We demonstrated that latent KSHV infection of endothelial cells induces aerobic glycolysis and decreases oxidative phosphorylation, the properties that define the Warburg effect, a common effect in over 90% of cancers (10). Additionally we show that KSHV induction of the Warburg effect is not universal but specifically occurs in endothelial cells, the relevant KS tumor-cell type.…”
Section: Discussionmentioning
confidence: 66%
“…We demonstrated that latent KSHV infection of endothelial cells induces aerobic glycolysis and decreases oxidative phosphorylation, the properties that define the Warburg effect, a common effect in over 90% of cancers (10). Additionally we show that KSHV induction of the Warburg effect is not universal but specifically occurs in endothelial cells, the relevant KS tumor-cell type.…”
Section: Discussionmentioning
confidence: 66%
“…RNA concentrations were assessed spectrophotometrically (UV-visible spectrophotometer, Cary 50 Scan, Varian) at 260nm. 400ng of total RNA was reverse transcribed (Superscript TM II, Invitrogen) and analyzed by Reverse Transcriptase-PCR (RT-PCR) (Hotstar Taq DNA polymerase; Qiagen, Hilden, Germany) using genespecific primers (Table 1) for collagen 1 (Col1α1), collagen II (Col2α1), aggrecan and transcription factor Sox9 , hypoxia inducible factor-1 (HIF) 1α isoform (Gao et al, 2005), metalloproteinase-2 (MMP2) (Shan et al, 2005), glycosylphosphatidylinositol-anchored cell surface protein CD24 (Fujita et al, 2005), glucose transporter (GLUT-1) (Robey et al, 2005), and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) as a housekeeping gene (Sanchez et al, 2005). The PCR fragments were resolved on a 1.5% agarose gel and stained with ethidium bromide.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…These include processes leading to enhanced oxygen delivery (angiogenesis), increased glycolytic metabolism and a switch from oxidative phosphorylation to anaerobic glycolysis (Gatenby and Gillies, 2004). The increased glycolytic activity under hypoxic conditions requires increased glucose uptake via glucose transporter proteins and increased expression of enzymes required for glycolysis (Akakura et al, 2001;Robey et al, 2005). These responses usually occur via changes in gene expression mediated by Hif-1a (Semenza, 2000;Semenza et al, 2000;Mahon et al, 2001).…”
Section: N H H-gd A204 A673mentioning
confidence: 99%